Development of 5-E Learning Cycle-Based Simple Chemistry Practicum Guideline Module for Eleventh Grade - Salsabila Syifaunnida; Agus Kamaludin (Postgraduate, University of Mataram, 2022)
The chemistry practicum activity in school is impossible due to the COVID-19 pandemic, whereas practicum is very important to train soft skills and understanding of chemistry materials. This research aimed to develop 5-e learning cycle-based simple chemistry practicum guideline module for students of class XI. The development model used was a 4-D development model. The quality of the product was assessed by one material expert, one media expert, five reviewers (chemistry teachers of high school), and responded by ten students of high school. The instruments used in the research were product quality assessment sheets using a Likert scale and student response sheets, in the form of a questionnaire, using the Guttman scale. The characteristics of the developed practicum module were in the form of a practicum module for hydrocarbons, thermochemistry, reaction rates, and chemical equilibrium, using simple tools and chemicals; being combined with the 5-e learning cycle model. The quality assessment on the practicum module, which was carried out by one material expert, media experts, and reviewers, gained 88.89. 95.83. and 94.00%. All assessments got a score with Very Good score. From these results, it can be concluded that the developed product is feasible to be used as a practicum guideline.